2013
DOI: 10.3103/s1067821213050088
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed strengthening of a diamond composite electrochemical coating with nanoparticles

Abstract: Results of investigations into strengthening the nickel host in the diamond composite electro chemical coating (DCEC) with nanodispersed particles are reflected. Diamond nanopowders of the detona tion synthesis, which were introduced into the DCEC through the electrolyte, are applied as the strengthen ing phase. As a result, the microhardness of the nickel host increased by a factor of 3, while the durability of tubular drilling tools after the deposition of the diamond coating increased by a factor of 4. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…It can be observed that there is an intense (111) crystallographic plane peak of Nanodiamond particles tend to form agglomerates, as reported by various authors [39,41,52]. Hence, the spheroids were aggregates of nanodiamonds at the top of the Cr-DND layer in the coating.…”
Section: Phase Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…It can be observed that there is an intense (111) crystallographic plane peak of Nanodiamond particles tend to form agglomerates, as reported by various authors [39,41,52]. Hence, the spheroids were aggregates of nanodiamonds at the top of the Cr-DND layer in the coating.…”
Section: Phase Analysissupporting
confidence: 59%
“…Ni-P coatings possess fairly high hardness, corrosion and wear resistance [36,37]. For this reason, a promising direction for the use of chromium-based CECs with DND and nickel-based CECs with DND, when certain conditions are met, is the coating of Ni as a matrix with DND, which does not provide the high strength characteristic for tool strengthening [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Hardness of the resulting coating binder is 201-228 HV. This is an obvious advantage of the obtained Sn-Cu-Co binder over nickel binders having the hardness of around 100 HV [4].…”
Section: Discussionmentioning
confidence: 95%
“…The layer consists of diamond particles enveloped in a metallic binder. To apply diamond-containing coatings on specially-shaped surfaces, various methods are used (in particular, electroplating and vacuum brazing) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation